Primary care genomic research: One eye on the future. Issue 2 (February 2021) - Evans, Philip H; Rafi, Imran; Hayward, Judith; Dineen, Molly; Walter, Fiona M.
The exceptional advances in genomic medicine in the last two decades, since the sequencing of the human genome, have already had a major impact on healthcare in the UK. Until recently this was predominantly in secondary and tertiary care, but we must now integrate 'mainstream' genomics in primary care. So far integration has of necessity been empirical, but must progress towards implementation research. We describe recent work undertaken by the RCGP and the NIHR CRN outlining areas where research is needed to fully integrate genomics into routine primary care and secure the future of these exciting developments.